Calomicrolaimus rugatus n. gen., n. sp. (Desmodoridae, Nematodes) from a sandy beach in Colombia - Lorenzen, S. (Mitt. Inst. Colombo-Alemán Invest. Cient. "Punta Betén", 1976)
Locality: Colombia; Cabinet:n1792
NeMys doc_id: 6860